Neurons for Ejaculation and Factors Affecting Ejaculation - Kiran Kumar Soni; Han-Seong Jeong; Sujeong Jang (Biology, 2022)
Ejaculation is a reflex and the last stage of intercourse in male mammals. It consists of two coordinated phases, emission and expulsion. The emission phase consists of secretions from the vas deferens, seminal vesicle, prostate, and Cowper’s gland. Once these contents reach the posterior urethra, movement of the contents becomes inevitable, followed by the expulsion phase. The urogenital organs are synchronized during this complete event. The L3–L4 (lumbar) segment, the spinal cord region responsible for ejaculation, nerve cell bodies, also called lumbar spinothalamic (LSt) cells, which are denoted as spinal ejaculation generators or lumbar spinothalamic cells [Lst]. Lst cells activation causes ejaculation. These Lst cells coordinate with [autonomic] parasympathetic and sympathetic assistance in ejaculation. The presence of a spinal ejaculatory generator has recently been confirmed in humans. Different types of ejaculatory dysfunction in humans include premature ejaculation (PE), retrograde ejaculation (RE), delayed ejaculation (DE), and anejaculation (AE). The most common form of ejaculatory dysfunction studied is premature ejaculation. The least common forms of ejaculation studied are delayed ejaculation and anejaculation. Despite the confirmation of Lst in humans, there is insufficient research on animals mimicking human ejaculatory dysfunction.